A Traceability Analysis of Monero’s Blockchain - Fischer, Amrit Kumar, Clement; Tople, Shruti; Saxena, Prateek (European Symposium on Research in Computer Security (ESORICS), 2017)
Privacy and anonymity are important desiderata in the use of cryptocurrencies. Monero—a privacy centric cryptocurrency has rapidly gained popularity due to its unlinkability and untraceablity guarantees. It has a market capitalization of USD 290M. In this work, we quantify the efficacy of three attacks on Monero’s untraceability guarantee, which promises to make it hard to trace the origin of a received fund, by analyzing its blockchain data. To this end, we develop three attack routines and evaluate them on the Monero blockchain. Our results show that in 88% of cases, the origin of the funds can be easily determined with certainty. Moreover, we have compelling evidence that two of the attack routines also extend to Monero RingCTs—the second generation Monero that even hides the transaction amount. We further observe that over 98% of the results can in fact be obtained by a simple temporal analysis. In light of our findings, we discuss mitigations to strengthen Monero against these attacks.We shared our findings with theMonero development team and the general community. This has resulted into several discussions and proposals for fixes.